1988
DOI: 10.1128/aem.54.1.158-164.1988
|View full text |Cite
|
Sign up to set email alerts
|

A suspension method to determine reuse life of chemical disinfectants during clinical use

Abstract: In-use testing of disinfectants is necessary to ensure efficacy over time. The current official procedure for testing disinfectants, the Association of Official Analytical Chemists (AOAC) use-dilution method, cannot be adapted to repeated sampling techniques of use-life testing. It is therefore necessary to use an alternative method when evaluating the activity of a disinfectant under actual use. The Clinical Research Associates (CRA) suspension method was developed to fill this need. It consists of adding 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Moreover, the ORP values and NO2- concentration were also significantly decreased, while pH was increased when organic matter was presented in PAW. The protective effects of organic materials on bacterial inactivation have also been reported in the case of other decontamination technologies including chlorine and non‐chlorine‐based chemical sanitiser (Robison et al , ; Virto et al , ). Moreover, the organic media are rich in nutrient components, which may support repair or regrowth of damaged bacteria (Ray & Speck, ).…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, the ORP values and NO2- concentration were also significantly decreased, while pH was increased when organic matter was presented in PAW. The protective effects of organic materials on bacterial inactivation have also been reported in the case of other decontamination technologies including chlorine and non‐chlorine‐based chemical sanitiser (Robison et al , ; Virto et al , ). Moreover, the organic media are rich in nutrient components, which may support repair or regrowth of damaged bacteria (Ray & Speck, ).…”
Section: Discussionmentioning
confidence: 77%
“…The laboratoryevaluation of the efficacy of the chemical disinfectantswas carried out using modified use-dilution test (Robinson et al, 1988). The test was repeated twice;once in the presence of organic matter and the secondtime in the absence of the organic matter.…”
Section: Evaluation Of the Efficacy Of Chemical Disinfectantsmentioning
confidence: 99%
“…The type of water has been shown to affect the activity of quaternary ammonium compounds (QAC). Robison et al. (1988) demonstrated that a QAC‐deionized water solution was much more effective than the same QAC diluted in tap water and reported log reduction differences of as much as 8 against Pseudomonas aeruginosa .…”
Section: Discussionmentioning
confidence: 99%